Peran Inklusi Keuangan dalam Memediasi Pengaruh Ekonomi Kreatif dan Blue Economy terhadap Kesejahteraan Ekonomi Nelayan Pesisir - Lubis, Nurliza; Ainul Yusna Harahap; Najihatul Faridy; Muh Rifai Arrasyid (Jurnal Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of Creative Economy and Blue Economy on the Economic Welfare of Coastal Fishermen, with Financial Inclusion as a mediating variable. Langsa City, Aceh, was chosen as the research site due to its significant marine potential, yet facing a decline in the number of fishermen from 3,194 in 2023 to 2,359 in 2024, despite the increasing contribution of the fisheries sector to regional GDP. This phenomenon highlights the need for an inclusive and sustainable coastal economic development strategy. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. A total of 150 fishermen were selected using Slovin’s formula and purposive sampling. The analysis covered outer model evaluation (validity and reliability) and inner model testing (direct effects, moderation, and mediation). The results reveal that the Blue Economy has a positive and significant effect on fishermen’s welfare, while the Creative Economy shows no significant effect. Financial Inclusion positively and significantly influences welfare, but its interaction with the Blue Economy is negative, indicating potential overcapitalization risks if financing is not environmentally sustainable. Mediation by Financial Inclusion is also significantly negative for the Blue Economy pathway, but not significant for the Creative Economy pathway. This study emphasizes the importance of strengthening the Blue Economy, providing supportive ecosystems for the creative economy, and implementing sustainability-based financial inclusion (green finance) to improve fishermen’s welfare without compromising marine ecosystems.